2022
DOI: 10.3344/kjp.2022.35.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of unipolar and bipolar spinal dorsal root ganglion radiofrequency thermocoagulation in the treatment of postherpetic neuralgia

Abstract: Background: Different views have been proposed on the radiofrequency treatment modes and parameters of radiofrequency thermocoagulation of the spinal dorsal root ganglion for the treatment of postherpetic neuralgia (PHN). It is urgent to identify a more effective therapy for patients with PHN. Methods: Patients who underwent radiofrequency thermocoagulation therapy for PHN were retrospectively reviewed and were divided into a radiofrequency thermocoagulation (CRF) and double neddles radiofrequency thermocoagul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It has been found that patients treated with bipolar RF-TC experience higher treatment efficiency, more significant pain relief, and longer maintenance than monopolar patients after surgery. In the present study, the recurrence rate of bipolar thermocoagulation was lower than that of monopolar, since bipolar RF needle thermocoagulation leads to a more radical destructive effect reaching a greater range of tissues, and therefore has a longer-lasting efficacy [ 19 ]. Patients with preoperative comorbidities such as hypertension, diabetes, coronary artery disease, or malignancy are more prone to recurrence than those without comorbidities [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that patients treated with bipolar RF-TC experience higher treatment efficiency, more significant pain relief, and longer maintenance than monopolar patients after surgery. In the present study, the recurrence rate of bipolar thermocoagulation was lower than that of monopolar, since bipolar RF needle thermocoagulation leads to a more radical destructive effect reaching a greater range of tissues, and therefore has a longer-lasting efficacy [ 19 ]. Patients with preoperative comorbidities such as hypertension, diabetes, coronary artery disease, or malignancy are more prone to recurrence than those without comorbidities [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although pulsed radiofrequency (PRF) has been shown to yield definite analgesic efficacy in treating herpes zoster-associated pain, some patients have insignificant pain relief and a high short-term recurrence rate after treatment, and often require additional pain relief treatment [ 15 17 ]. Radiofrequency thermocoagulation (RF-TC) enables the destruction of the DRG with significant pain relief and high efficiency [ 18 , 19 ]. Therefore, for patients with PHN, RF-TC may become a effective percutaneous minimally invasive surgical modality to relieve the pain, reduce the recurrence rate, improve sleep, and enhance the quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…Ultimately, it reduces the incidence, severity, and duration of pain and limits neuronal damage [ 1 , 8 ]. The replicated latent VZV leads to inflammatory sensory or motor neural damage of the peripheral and central nervous systems, resulting in zoster-associated pain (ZAP) or postherpetic neuralgia (PHN) [ 1 , 11 ]. In addition to the therapeutic effect of antivirals on HZ itself, the reduction and prevention of ZAP or PHN are also important clinical perspectives [ 1 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…PRF mainly emits pulses to act around the nerve tissue through the radiofrequency instrument and creates a high voltage so that the heat generated by the pulse current near the affected tissue can be diffused. The local temperature does not exceed 42 °C, avoiding the damage caused by high temperature to the nerve, and the nerve tissue does not degenerate and can play a protective role in integrating nerve functions to avoid postoperative sensory and motor nerve abnormalities caused by nerve injury [18,19]. Kagan et al [20] reported that the ultrastructural assessment of PRF lesions in rat lower extremity nerve showed that PRF treatment did not cause the unmyelinated nerve fibers to ultrastructurally impair.…”
Section: Introductionmentioning
confidence: 99%